FACTORS THAT AFFECT CONSUMERS' PURCHASE DECISIONS ON TIKTOK SHOP, CONVENIENCE, USE, TRUST, AND QUALITY OF SERVICE IN YOGYAKARTA STUDENTS - Elisabet Anjelita Suryanti; Rinaldi Rinaldi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Abstract The development of social commerce has encouraged the increase in online shopping activities through platforms such as TikTok Shop among students. Ease of access, digital interaction, and services offered have the potential to influence consumers' purchasing decisions in making online transactions. This study aims to analyze the influence of ease of use, trust, and service quality on student purchasing decisions in Yogyakarta on the TikTok Shop platform. The research method used was quantitative with a causal associative design and a cross-sectional approach. The research sample amounted to 50 respondents who were selected using the purposive sampling technique, namely students who had made purchases through TikTok Shop. Data collection was carried out using a Likert scale questionnaire and analyzed through multiple linear regression with the help of SPSS software. The results of the study showed that ease of use, trust, and service quality partially had no significant effect on purchase decisions. Simultaneously, the three variables also had no significant effect with a determination coefficient value of 5.9%, which suggests that purchasing decisions were more influenced by other factors outside the research model. These findings confirm that factors such as price, promotion, trends, and content attractiveness have a more dominant role in driving student purchasing decisions on the TikTok Shop platform.